(untitled) (Dimensión Antropológica, 2022)
This work attempts to show that in the colonial society of Sonora the dominant regional groups were divided and their contradictions hindered their colonizing activities. There were three groups: the missionaries of the Society of Jesus, the civilian colonists and the military ones. The first two of these competed for control of the indigenous communities and their resources, while the third, more focused on productive and commercial activities, endangered the internal peace of the province and the defense of its borders against Apache attacks. Thus, in promoting their particular immediate interests, the three groups offered broad opportunities to the indigenous communities of successfully defying the colonial socio political order.